The Influence of Customer Experience, Brand Awareness and Atmosphere Cafes on Gen Z Consumer Loyalty in Cafes in Kediri City - Lissa Aprilia; Hery Purnomo (Journal of International Conference Proceedings, 2025)
Generation Z consumer loyalty is an important concern for café business actors because this demographic group is increasingly playing a role in shaping market trends and purchasing patterns. This study aims to analyze the influence of customer experience, brand awareness, and café atmosphere on the loyalty of Generation Z consumers in Kediri City. A quantitative approach was used with a purposive sampling technique on 100 respondents who had visited and made purchases at local cafes. Data collection was carried out through a Likert scale questionnaire, then analyzed using multiple linear regression. The results showed that customer experience and brand awareness had a positive and significant effect on loyalty, while the café atmosphere had no significant influence. Customer experience is the most dominant factor in influencing loyalty. These findings indicate that improving customer experience and strengthening brand awareness need to be strategic priorities for café businesses in building Generation Z consumer loyalty. Further research can expand the context of the region or age group to improve generalization.